Pengembangan Aplikasi "ALBI" (Kenali Kisah Nabi) pada Pembelajaran PAI Kelas II Sekolah Dasar - Anisa Oktaefi, Ayu; Jannah, Firda Tri Mahbubatul; Erwanti, Gistia; Aeni, Ani Nur (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This research focuses on the development of an application called "ALBI" (Get to Know the Stories of the Prophets) as an innovative and interactive learning medium for the Islamic Religious Education (PAI) subject, targeting second-grade elementary school students. The research method employed is Design and Development (D&D). The application aims to introduce students to the stories of the prophets and the technological advancements during their respective eras. A trial conducted at SD Negeri Gunungsari showed an improvement in students' learning interest and comprehension. Data were collected through observations and questionnaires distributed to both students and subject matter experts. The results indicate that the "ALBI" application received a positive response and was considered effective in assisting students in understanding the stories of the prophets. The development of this technology-based learning medium is expected to serve as an innovative solution to enhance the quality of Islamic Religious Education at the elementary school level.